ANALYSIS OF RACIAL DISCRIMINATION BY SUPPORTERS AGAINST PLAYERS IN FOOTBALL SPORTS - Rahmat Muliana (el-Nizami : Jurnal Manajemen Pendidikan, 2024)
Racial discrimination or racism is a belief system that has become an ingrained doctrine stating that biological differences are related to the human race. A certain race considers itself superior and has the right to control others so that humans always consider a group, group, religion, or race to be the most correct and powerful. Then they underestimate others. This study aims to analyze racial discrimination by supporters against players in soccer. The writing method used is literature study. The analysis carried out is based on data or content from references and is supplemented with an analysis of the phenomenon of racism that occurs in soccer. The method used is literature study. Based on the results of the study and data processing, it can be concluded that racial discrimination or racism can happen to anyone and be carried out by anyone. Racism by supporters against players, racism by players against other players. Racism by supporters against the crew of the soccer team. The perpetrators are not only supporters, but can also come from prominent people. The racism that occurs is more directed at a race or physical form that can be seen directly with the eye. Racism occurs due to many factors, depending on the perpetrators and recipients of racial discrimination.